Back Cover: Cofactor‐Free Light‐Driven Whole‐Cell Cytochrome P450 Catalysis (Angew. Chem. Int. Ed. 3/2015). Issue 3 (12th December 2014) - Park, Jong Hyun; Lee, Sahng Ha; Cha, Gun Su; Choi, Da Som; Nam, Dong Heon; Lee, Jae Hyung; Lee, Jung‐Kul; Yun, Chul‐Ho; Jeong, Ki Jun; Park, Chan Beum
<x xml:space="preserve">Abstract</x> A light‐driven platform for cofactor‐free, whole‐cell P450 biocatalysis is described by C.‐H. Yun, K. J. Jeong, C. B. Park, and co‐workers in their Communication on page 969 ff. This novel platform does not require any labor‐intensive and time‐consuming pretreatments and is applicable to any type of bacterial and human cytochrome P450s. Instead of expensive cofactors, the use of an inexpensive photosensitizer, visible light, and a whole‐cell system leads to a cost‐effective, scalable, and sustainable process for P450‐catalyzed reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>